Clinical analysis of blood traces of rats after subcutaneous implantation of Nd-Fe-B magnets with protective PVD ZrN coatings - Kutsevliak, V.I.; Starikova, S.L.; Taran, A.V.; Misiruk, I.O.; Starikov, V.V.; Baturin, A.A.; Konotopska, N.V.; Dushyk, L.M.; Cherkova, N.V. (Вопросы атомной науки и техники, 2021)
It is possible to increase the effectiveness of treatment of various anomalies of occlusion with the help of orthodontic appliances, including permanent magnets as components. But a significant disadvantage of magnetic materials is low corrosion resistance, which can be prevented by applying to the magnets various PVD protective coatings leading to passivation of the surface of the magnetic material. The effect of Nd-Fe-B magnets with and without protective ZrN coating after subcutaneous implantation in rats on the results of laboratory blood tests has been evaluated.